Postoperative mortality in orthopaedic and trauma service: a retrospective trend analysis from a developing nation - Malika Hameed; Mohammad Khozema Safri; Ebadullah Shahood; Sijal Akhtar Sheikh; Akbar Jaleel Zubairi; Mohsin Nazir Butt (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate postoperative mortality trends and contributing factors in patients undergoing orthopaedic and trauma surgeries in a tertiary care setting. Method: The retrospective audit was conducted from January to March 2021 at Aga Khan University Hospital, Karachi, and comprised data from January 1, 2016, to December 31, 2020, of patients who underwent any orthopaedic or trauma-related surgical procedure and died either during hospital stay or within 30 days postsurgery. Mortality was categorised into early (less-than-or-equal 5 postoperative days) and late (>5 days) deaths to identify patterns and contributing factors. Data was analysed using SPSS 23. Results: Among the 14,917 orthopaedic and trauma surgeries performed, there were 85(0.56%) postoperative deaths with the mean age of patients being 58.35±23.52 years. There were 52(61.18%) males and 48(56.47%) were aged >60 years. Emergency admissions accounted for 66(77.65%) cases. Infections 29(34.12%) and fragility fractures 24(28.24%) were the most common diagnoses, and cardiopulmonary complications occurred in 82(96.43%) cases. Mortality was categorised as early in 39(45.88%) cases and late in 46(54.12%). Most deaths occurred in intensive care settings 48(56.47%). Conclusion: Postoperative mortality in orthopaedic and trauma surgeries was found to be low. Perioperative care, risk stratification and targetted interventions for high-risk groups are recommended. Key Words: Orthopaedic procedures, Trauma, Mortality, Postoperative complications, Risk factors, Developing countries.